The impact of automation on the safety of drug dispensing in nursing homes - Idoia Beobide Telleria; Alex Ferro Uriguen; Blanca Miró Isasi; Silvia Martínez Arrechea; Maria Isabel Genua Goena (Farmacia Hospitalaria)
Objective: To compare the frequency and seriousness of notified dispensing errors in nursing homes when medication is dispensed manually versus automatically using a specifically selected automatic dispensing system. Method: A pre-post retrospective observational study in 7 nursing homes. We compare voluntarily notified dispensing errors in a manually dispensed weekly system on the one hand (year 2013), with an Automated Tablet Dispensing and Packaging System Xana4001U2 Tosho® for oral solid drugs used in combination with a manual system for other drug forms (year 2015), on the other. We analyze patient function, cognition and pharmacological data in two time periods. Results: Residents’ mean age (83.9 vs 83.6 years; p > 0.05) and physical functioning (Barthel index 41.8 vs 44.2; p > 0.05) were similar, but not cognitive functioning (MMSE 20.3 vs 21.7; p < 0.0,5). During the year previous to the automated dispensing, 408 errors were detected with the manual system, whereas only 36 were detected in the following year with the automated system. This represents a reduction of 91% in dispensing errors. 43 errors reached the patient during the manually dispensing versus 6 during the automated year. And 5 errors versus 1 required monitoring. Conclusions: The introduction of an automatic tablet dispensing and packaging system has shown to be an important improvement in safety in the dispensing and administration of solid drugs in nursing homes. The voluntary notification of errors has permitted the comparison of safety during two time periods with different dispensing systems.